The design of virtual lower limb rehabilitation for post-stroke patients - Lee Wei Jian; Syadiah Nor Wan Shamsuddin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Stroke is one of the leading causes that elicits to disability for adults over a long period. Post-stroke patients often have difficulties with joints and muscles in their legs, which prevents them from moving around. Lower limb rehabilitation helps to regain normal mobility and functionality of patients such as standing, walking and climbing stairs. The implementation of virtual reality in stroke rehabilitation helps to encourage patients on frequent engagement with exercise. This paper briefly presents the ongoing research regarding lower limb rehabilitation systems for post-stroke patient in virtual reality environment to provide an overview of the conceptual design, limitations, and suggestions for future work in this direction.